2023
DOI: 10.1094/pdis-06-22-1347-re
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Disease Scoring Method to ScreenEucalyptusfor Resistance Against the Aggressive Leaf PathogenTeratosphaeria destructans

Abstract: Shoot and leaf blight caused by Teratosphaeria destructans is one of the most devastating foliar diseases of Eucalyptus. Therefore, breeding for resistance to this disease is considered urgent. Differences in susceptibility to T. destructans have been observed in the field, but a robust inoculation protocol has, until recently, been unavailable and a disease scoring method for precise phenotyping has not been established. A first objective of this study was to determine the optimal conidial concentration for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…During the sampling process in the current study, we found that the severity caused by each species of T. epicoccoides and T. destructans on different genotypes of E. urophylla × E. grandis were different. Research results showed that significant differences in resistance exist among the six tested E. grandis × E. urophylla genotypes to the inoculated T. destructans [ 71 ]. It is suggested that breeding and selection of Eucalyptus tolerant/resistant species, hybrids and clones are needed for the future management of leaf diseases caused by Teratosphaeria species [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the sampling process in the current study, we found that the severity caused by each species of T. epicoccoides and T. destructans on different genotypes of E. urophylla × E. grandis were different. Research results showed that significant differences in resistance exist among the six tested E. grandis × E. urophylla genotypes to the inoculated T. destructans [ 71 ]. It is suggested that breeding and selection of Eucalyptus tolerant/resistant species, hybrids and clones are needed for the future management of leaf diseases caused by Teratosphaeria species [ 41 ].…”
Section: Discussionmentioning
confidence: 99%